Implementation of Islamic Ecotheology in the Hidden Curriculum of Traditional Islamic Boarding School Education - Antiti Armilah; Abu Warasy Batula; Nurlaila Turohmah; Robiatul Adawiyah Ramadhani; Yahya Rafi Sya’bani; Rizki Abdillah (Civilization Research: Journal of Islamic Studies, 2026)
This study analyzes  the implementation of Islamic ecotheological values in farming practices in traditional Islamic boarding schools as a hidden curriculum for shaping student’s character . The global ecological crisis, rooted in the anthropocentric paradigm calls for  spiritual reconstruction through experience-based Islamic education. Yet, the role of traditional Islamic boarding schools without formal environmental programs is often overlooked in eco-Islamic boarding school discourse. Employing  a qualitative case study approach at Azziyadah Islamic Boarding School, Cirebon, data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed thematically using NVivo 12. The findings reveal ree that farming practices are not merely economic activities, but rather a medium for spiritual education that encompasses three dimensions of the hidden curriculum: direct instruction, religious reflection, and the exemplary behavior of the kyai (uswah hasanah). ogether, these dimensions synergistically internalize the values of tauhid, amanah, khalifah, and gratitude, aligning with principles of curriculum relevance and integration.  The novelty of this research lies in revealing the mechanism of organic ecological value transmission through cultural obedience (ta’dzim) in traditional Islamic boarding schools. This research indicates  that this hidden curriculum model can be replicated as an alternative policy recommendation for the Ministry of Religious Affairs and related institutions to strengthen environmentally conscious character education in contemporary Islamic educational settings, complementing existing structural approaches.